Jurisprudence Provisions Related to Reservation - Hamid , Hamid (Islamic Sciences Journal, 2023)
ABSTRACT Islamic jurisprudence deals with people's problems and relieves the pain of living. The inquirer about knowledge when researching matters of jurisprudence must delve into the issues that have occurred. I state in the research entitled (Jurisprudential Rulings Related to Stone) about the definition of reservation, the ruling on the emancipation of the bankrupt after reservation , and the settlement of deferred debts by death, and about preventing the debtor from traveling until his rightful owner is documented. Then the conclusion in which I mentioned the most important results that I reached at and may God bless our master Muhammad and his family and companions as a whole.